Performance Analysis of Premium and Medium Rice Supply Chain of Bulog in Bogor - Juliawan, Dwi; Syarief, Rizal; Findi, Muhammad (Amkop Management Accounting Review (AMAR), 2025)
This study aims to evaluate the performance of Bulog's rice supply chain in Bogor, focusing on two product categories: premium rice and medium rice under the SPHP program. The objective is to identify strengths and gaps in operational performance across key supply chain metrics and provide actionable insights for future improvement. A mixed-methods approach was used, combining qualitative interviews with supply chain stakeholders and quantitative analysis using the SCOR-AHP (Supply Chain Operations Reference – Analytical Hierarchy Process) framework. Performance indicators, such as Perfect Order Fulfillment (POF) and Upside Supply Chain Adaptability (USCA), were analyzed using benchmark comparisons and priority weight calculations. The overall performance of Bulog's rice supply chain in 2024 was rated very good. Premium rice achieved a performance score of 95.31%, while medium rice (SPHP) scored 86.61%. However, medium rice showed notable weaknesses in POF (72.5%) and USCA (46.67%), indicating challenges in order fulfillment precision and responsiveness to sudden demand increases. In contrast, premium rice performed better in these areas, with a POF of 96.55% and a USCA rating of 71.43%. The findings highlight areas for operational refinement, particularly in improving adaptability and delivery accuracy. These insights are valuable for supply chain practitioners and policymakers seeking to enhance national food distribution systems.